Penerapan Prinsip Paradigma Good Governance dalam Implementasi Program Puspaga Balai RW: Studi Kasus Kelurahan Banyu Urip, Kecamatan Sawahan Kota Surabaya - Muhammad Faza Zakiy Makarim; Indira Arundinasari (IAI Nasional Laa Roiba Bogor, 2024)
Domestic violence or (KDRT), is a phenomenon of social problems within the family sphere that is rife in Indonesia, especially in big cities such as Surabaya as a result of economic problems, overcrowding and other problems. Responding to this problem, the Surabaya City Government initiated a Family Learning Center (Puspaga) program which was inaugurated in 2017. One of the areas that held the Puspaga program was RW 3 Banyu Urip Village, Sawahan District, Surabaya City. This study aims to reveal the principles of good governance contained in the implementation of Puspaga program policies in RW 3. Policy implementation analysis uses Edward III's policy implementation model which consists of four aspects, namely communication, resources, disposition, and bureaucratic structure. The research uses qualitative approaches and descriptive methods in the elaboration of research data. Research data collection techniques were carried out on secondary data in the form of literature studies, and on primary data using in-depth observation methods and closed interviews. The data analysis technique uses the Miles and Huberman analysis model. The research suggests that the Puspaga policy implementation program has run well and meets six principles in good governance, namely the principles of professionalism, accountability, transparency, excellent service, democracy and participation, efficiency and effectiveness, rule of law, while in the principle of transparency no data on budget resources was found due to limited researchers in finding informants.